MAPPING VALUE CHAIN SEBAGAI OPTIMALISASI PENGEMBANGAN KAMPUNG BATIK TULIS DI SURABAYA - Sujani Sujani; M S Arif; Agus Sarwo Edi (Media Mahardhika, 2019)
The creative industry which is one of Indonesia's valuable cultural heritages and has been known throughout the world is Batik. The culture of making batik has also been occupied by some residents of Surabaya, but only its presence has not been widely exposed. However, its existence is still not developed optimally, the Surabaya city government initiated the Putat Batik House as the center handmade Batik Village in Surabaya. The purpose of this research is to obtain the formulation of strategies that can be applied to maximize the utilization of potential effort to develop the Medium Creative Industry (IKM) of handmade batik in Surabaya. The value chain mapping is carried out as a basis of information on value formation in a creative industry which can be seen from the aspects of creation, production, distribution and commercialization. Information of value chain mapping is valuable for an input to determine the strategic factors of batik industry village. The results of the study were obtained, that a value chain process of the IKM handmade batik activities began from material planning to network marketing. The total internal matrix value of 4.013 is classified as "Strong" and the total external matrix value of 4,286 shows the response to the external environment is classified as "High". If the total score of internal and external factors is mapped in the matrix, then the position of the company in the "First" quadrant is a growth strategy, namely: concentration on human resources, skills, target markets, market expansion and networking and product development.